Design and Construction of A Pyrolysis Device for Laboratory- scale Liquid Smoke Production Applications - Jannah, Miftahul; Saiya, Abdon; Karundeng, Marlina; Tengkar, Soenandar; Kamaruddin, Kamaruddin; Mustapa, Mustapa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Liquid smoke has been widely applied in various fields. Several studies have developed methods, tools and materials for making liquid smoke. This research aims to design a tool for making liquid smoke using a simple pyrolysis method on a laboratory scale. The goal is that this tool can be used by students for practicums to further increase students' insight and skills regarding liquid smoke. The stages of this research start from literature study, technology design, tool fabrication and testing as well as the evaluation stage. The results obtained in this research are that a liquid smoke pyrolysis device has been successfully made with a capacity of 6 kg. Based on the test results, grade 3 liquid smoke was produced.